Polarisasi Interaksi Sosial Keagamaan Masyarakat Siwalankerto di tengah Pandemi Covid-19 - Azizah, Siti; Aziz, Abd. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2022)
There are two focus problems in this study, namely: How is the process of changing the pattern of socio-religious interaction and what is the form of polarization of socio-religious interactions during the Covid-19 pandemic in Siwalankerto Village, Wonocolo District? This research was conducted using qualitative research methods and in analyzing this study using the AGIL-Talcott Parson theory. From the results of the study, it was found that there were new patterns in the socio-religious interaction of the Siwalankerto community since the covid-19 pandemic. This new pattern began to become new values in socioreligious life when the government made several policies and regulations relating to the handling of the covid 19 pandemic. With the changing patterns of interaction and the community must be able to adapt to the current pandemic conditions. Changes in socio-religious interactions during the COVID-19 pandemic occurred when people had to adjust to government policies regarding the community in their activities, including in socio-religious activities and the application of strict protocols in every activity, including the implementation of religious rituals. With the COVID-19 pandemic, religious ritual activities which are usually carried out together and between religious activities and social interaction have become a single unit in society, now must change. Government policies and regulations for worship must be carried out in their respective homes so that there is a polarization of social interaction and religious practice during the COVID-19 pandemic